Influence of X-ray irradiation on the optical absorption edge and refractive index dispersion in Cu₆PS₅I-based thin films deposited using magnetron sputtering - Studenyak, I.P.; Kutsyk, M.M.; Bendak, A.V.; Izai, V.Yu.; Kus, P.; Mikula, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Cu₆PS₅I-based thin films were deposited using non-reactive radio-frequency magnetron sputtering. Structural studies of thin films were performed by scanning electron microscopy, and their chemical composition was determined using energy-dispersive X-ray spectroscopy. As-deposited thin films were irradiated with wideband radiation of a Cu-anode X-ray tube at different exposure times. Optical transmission spectra of X-ray irradiated Cu₅.₅₆P1.₆₆S₄.₉₃I₀.₈₅ thin films were measured depending on irradiation time. The Urbach absorption edge and dispersion of refractive index for X-rays irradiated Cu₅.₅₆P1.₆₆S₄.₉₃I₀.₈₅ thin films were studied. It has been revealed that the nonlinear decrease of energy pseudogap and the nonlinear increase of refractive index occur with the increase of X-ray irradiation time.